A critical discourse analysis of Bintang Emon’s humor discourse entitled ‘Ga Sengaja’ - Rahman, Riska; Hidayat, Didin Nuruddin; Alek, Alek (Englisia: Journal of Language, Education, and Humanities, 2021)
This study aims to investigate the text, the discourse practice, and the sociocultural practice of Bintang Emon’s discourse humor video entitled “Accidentally (Ga Sengaja),” posted on his Instagram platform. To analyze the data, the qualitative descriptive method was used in this study. The data were obtained from the video transcript of Bintang Emon accessed from Instagram. The data were then analyzed by using Norman Fairclough’s discourse analysis model. Moreover, the techniques used were observing, interpreting the data by analyzing the text, which was seen from three elements such as Representation, Relation, and Identity; analyzing the discourse practice which focused on production, consumption, reproduction of the text; and analyzing the socio-cultural practice of the discourse humor, and the last is concluding. The result of this study showed that Bintang Emon used more rhetorical figures in his discourse in the analysis of text level. He delivered his criticism with good word choices and conveyed some analogies to make the audiences agree with what he said. The intention of his complaint regarding Novel Baswedan’s acid attack case was expressed implicitly so that the audiences cannot predict his intention if they only look at it from his caption. In the level of discourse practice, he successfully represented most of the citizens’ criticism against the case. Furthermore, he took his right to freedom of speech to deliver his thought in a humorous style.